Optimization of Natural Adhesive Type and Concentration on Characteristics of Corn Cob Biobriquettes - Adam Yonanda; Elvianto Dwi Daryono (G-Tech: Jurnal Teknologi Terapan, 2025)
This study aims to evaluate the effect of wheat flour, starch, and sago adhesive variations on the characteristics of corn cob-based biobriquettes. Against the backdrop of fossil fuel scarcity and the abundance of corn cob waste, this research offers a solution to utilize the waste as an alternative fuel in the form of briquettes. The use of adhesives is an important element in the manufacture of quality briquettes. Adhesives not only play a role in maintaining the density of briquettes, but also affect the overall quality of the product. Different types of adhesives will result in different briquette quality, due to the different chemical compositions among the adhesives. The use of three types of adhesives with varying concentrations is expected to affect the quality of the briquettes based on SNI 01-6235-2000 standards. Testing the characteristics of biobriquettes includes moisture content, ash content, calorific value, and combustion rate. The results of this study found that the most optimal biobriquettes were 15% tapioca adhesive with the highest calorific value of 5563.13 cal/g, water content of 1.96%, ash content of 3%, volatile matter content of 5.76%, bound carbon content of 89.28%, and burning rate of 0.49 g/min. The biobriquettes have met SNI-01-6235-2000.